Illustres appendix: córki szlacheckie Kasprowi Niesieckiemu i Adamowi Bonieckiemu nieznane - Marczewski, Jarosław (Archiwa, Biblioteki i Muzea Kościelne, 2021)
The extreme scholarly importance of Kasper Niesiecki and Adam Boniecki's armorials makes those books an ever-valid point of reference for any genealogical research. Nonetheless, both armorials sufler numerous deficiencies, caused by the specilic naturę of the materials which the scholars madę use of. Defects are particularly freąuent in the cases of noblemen's daughters who were nuns. However, excellent materials which afford the opportunity to supplement these existing faults can be found in the admission books of individual cloisters. This is because a certain number of entries contain not only the nuns' names, but also valuable and informative remarks with regard to their families. Admission books have been preserved very rarely, however. Fortunately, there exists one book which used to belong to the cloister of the Sisters of St. Bridget in Lublin, Poland. Based on this book, it was possible to fili in the armorials' information in 40 cases of noblewomen who were nuns.